Validation of the Double Mediation Model of Workplace Well-Being on the Subjective Well-Being of Technological Employees - Chang, Shu-Ya; Hsu, Hsiang-Chen (Frontiers in Psychology, 2022)
In recent years, workplace well-being has been a popular research topic, because it is helpful to promote employees’ welfare, thereby bringing valuable personal and organizational outcomes. With the development of technology, the technology industry plays an important role in Taiwan. Although the salary and benefits provided by the technology industry are better than other industries, the work often requires a lot of time and effort. It is worth paying attention to whether a happy workplace will bring subjective well-being for the technology industry in Taiwan. This study explored the influence of workplace well-being, job involvement, and flow on the subjective well-being. The research was conducted by a questionnaire survey. A total of 256 employees in the technology industry in the Nanzi Processing Zone in Kaohsiung City, Taiwan were surveyed. Collected data were analyzed by statistical methods, such as multivariate and structural equation models. The study results indicated that workplace well-being, flow, and job involvement have a positive and significant impact on the subjective well-being. In addition to having a direct impact on subjective well-being, flow is also a significant variable to mediate the impact of workplace well-being to subjective well-being. In addition, job involvement also affects subjective well-being through flow, which means that the state of selflessness at work is the most important factor affecting subjective well-being. Finally, based on the research findings, the researcher provided practical suggestions to the government and the technology industry.